Clinician's opinion about critical risk results proposed by the Croatian Chamber of Medical Biochemists : a survey in one Croatian tertiary hospital - Šonjić, Pavica, medicinska biokemičarka (Array, 2019)
It has been recommended that each laboratory modify their critical result reporting practices to reflect the clinical needs of theirpatient populations. The aim of this survey was to assess how well critical laboratory values defined by the Croatian Chamber of Medical Biochemists(CCMB) correspond to the needs of the physicians at University hospital “Sveti Duh” (Zagreb, Croatia).Materials and methods: We conducted a survey among physicians from five departments in our hospital. Physicians were asked general questionsabout critical risk results (if and how they want to be informed). A list of critical risk results defined by the CCMB was offered and physicians wereasked to revise the existing critical risk results and suggest adding new parameters. Obtained data were presented as numbers. Where the numberof observations was low, ratios were used.Results: Survey response rate was 43% (52/121). Majority (48/52) wants to be informed of critical risk results, either personally (31/48) or througha colleague (32/48). They prefer to be informed about critical risk results of prothrombin time, platelet count, haemoglobin, glucose, creatinine, sodiumand potassium. Revisions in the CCMB critical risk result list are proposed by 13 out of 48 physicians. Neonatologists approved the CCMB’s list.Conclusions: Although most critical risk results defined by the CCMB correspond well to the needs of the physicians in our hospital, some revisionsare necessary to meet the particular needs of individual departments. Communication of critical risk results to those who have requested laboratorytesting is highly appreciated practice.